(untitled) (Medico Legal Update, 2021)
Background: This study aimed to provide basic data for the development of COVID-19 infection management educational programs by confirming the factors that affect the performance of COVID-19 infection management administration in general hospitals. Method: Data was collected from administrative staff at 192 general hospitals by means of a structuralized questionnaire, and SPSS Ver. 21.0 software was used for data analysis. Conclusion: The extent of knowledge and execution of COVID-19 infection management processes by administrative staff in general hospitals was positively correlated with the extent of educational demand for COVID-19 infection management, with explanatory power of 16.7%. It is necessary to include factors including COVID-19 transmission route, transmission prevention, and staff safety in COVID-19 infection management educational program administration. In addition, it is essential also to performance COVID-19 infection management education